2014
DOI: 10.1002/anie.201408730
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Construction of Vicinal Tetrasubstituted Stereocenters by the Mannich Reaction of Silyl Ketene Imines with Isatin‐Derived Ketimines

Abstract: A highly enantioselective Mannich reaction of silyl ketene imines with isatin-derived ketimines has been realized by using a chiral N,N'-dioxide/Zn(II) catalyst. A variety of β-amino nitriles containing congested vicinal tetrasubstituted stereocenters were obtained with excellent outcomes (up to 98 % yield, >19:1 d.r. and 99 % ee). Based on the experimental investigations, a possible transition state has been proposed to explain the origin of the asymmetric induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(29 citation statements)
references
References 79 publications
0
26
0
3
Order By: Relevance
“…[6] Thes ynthesis of C3-substituted oxindoles carrying two or more contiguous stereogenic centers is equally demanding,although afew impressive examples are known. [7] Ac atalytic method that affords 3-fluorooxindoles exhibiting vicinal chiral centers with one being fluorinated would achieve both tasks at once and significantly widen the scope and availability of this important class of compounds. [8] In this regard, Trostsasymmetric allylic alkylation (AAA) would be afavorable reaction owing to its outstanding value in natural product synthesis.…”
mentioning
confidence: 99%
“…[6] Thes ynthesis of C3-substituted oxindoles carrying two or more contiguous stereogenic centers is equally demanding,although afew impressive examples are known. [7] Ac atalytic method that affords 3-fluorooxindoles exhibiting vicinal chiral centers with one being fluorinated would achieve both tasks at once and significantly widen the scope and availability of this important class of compounds. [8] In this regard, Trostsasymmetric allylic alkylation (AAA) would be afavorable reaction owing to its outstanding value in natural product synthesis.…”
mentioning
confidence: 99%
“…By treatment of 3.6 mmol of 1 a and 3.5 mmol of 2 a in the presence of 0.01 mol % L 2 ‐RaPr 3 /Mg(OTf) 2 complex, 1.08 g 3 a was obtained with 92 % ee (95 % yield, Scheme a). The product could also be reduced by Cp 2 TiCl 2 in situ, and then further converted efficiently to α‐amino amide 5 a and 1,2‐diamine 6 a by treating with H 2 O 2 and NaBH 4 , respectively (Scheme b). The convenient gram‐scale synthesis in low catalyst loading and useful transformations indicated a potential of this methodology in medicinal chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…As an example, in 2015 Feng et al reported the enantioselective Mannich reaction of N- Boc-isatin imines 3 with silyl ketene imines 27 catalyzed using a combination of Zn(OTf) 2 and chiral N,N’- dioxide ligand 28 [48]. As shown in Scheme 9, this remarkable process afforded a wide range of chiral β-amino nitriles 29 exhibiting two vicinal tetrasubstituted stereocenters as almost single diastereomers (>90% de) in both uniformly excellent yields (90–98%) and enantioselectivities (94–99% ee).…”
Section: Reviewmentioning
confidence: 99%